2014
DOI: 10.1002/cne.23567
|View full text |Cite
|
Sign up to set email alerts
|

Systematic comparison of adeno‐associated virus and biotinylated dextran amine reveals equivalent sensitivity between tracers and novel projection targets in the mouse brain

Abstract: As an anterograde neuronal tracer, recombinant adeno-associated virus (AAV) has distinct advantages over the widely used biotinylated dextran amine (BDA). However, the sensitivity and selectivity of AAV remain uncharacterized for many brain regions and species. To validate this tracing method further, AAV (serotype 1) was systematically compared with BDA as an anterograde tracer by injecting both tracers into three cortical and 15 subcortical regions in C57BL/6J mice. Identical parameters were used for our seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 94 publications
(157 reference statements)
3
34
1
Order By: Relevance
“…Injection of adeno-associated virus (AAV) can retrogradely label cells whose axons target the region injected; the number of retrograde labeled cells depends on the particular brain region and other factors (Harris et al, 2012;Wang et al, 2014). After sSC injections of virus encoding nonconditional fluorescent protein expression, we observed retrogradely labeled neurons in several regions known to provide input to the sSC: retina, layer 5 of visual cortex, and PBg.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Injection of adeno-associated virus (AAV) can retrogradely label cells whose axons target the region injected; the number of retrograde labeled cells depends on the particular brain region and other factors (Harris et al, 2012;Wang et al, 2014). After sSC injections of virus encoding nonconditional fluorescent protein expression, we observed retrogradely labeled neurons in several regions known to provide input to the sSC: retina, layer 5 of visual cortex, and PBg.…”
Section: Methodsmentioning
confidence: 90%
“…5 A, B). Previous studies of (unidentified) mouse sSC cells also described directionally selective neurons but differed in whether the preferred directions of these cells were uniformly distributed (Wang et al, 2010) or strongly biased for upward motion (Dräger and Hubel, 1975). We found that the preferred directions of directionally selective WF cells (those with DSI Ͼ 0.25), but not the other cell types, deviated significantly from equal distribution into the four cardinal directions ( p Ͻ 0.01; Fig.…”
Section: Distinct Ssc Cell Types Respond To Distinct Characteristics mentioning
confidence: 99%
See 1 more Smart Citation
“…Their companion paper, Wang et al, (2014) "Systematic comparison of adeno-associated virus and biotinylated dextran amine reveals equivalent sensitivity between tracers and novel projection targets in the mouse brain", provided the crucial technical foundation for Oh et al, (2014). They compared anterograde neuronal tracing using either EGFP-expressing AAV, or biotinylated dextran amine (BDA).…”
mentioning
confidence: 99%
“…While both methods gave robust anterograde labeling, minor retrograde labeling of neurons was also observed for both AAV and BDA. Oh et al (2014) defined the axonal projections from 295 non-overlapping brain regions using an AAV vector expressing EGFP under the control of the human Synapsin I promoter. High-resolution projection data obtained from both cortical and subcortical mapping, were integrated with 863 grey-matter zones annotated within the Allen Reference Atlas.…”
mentioning
confidence: 99%